Amenazas, Vulnerabilidades Y Adaptación A Inundaciones En El Marco Del Cambio Climático: Caso De Estudio Machala - Reisancho Puetate, Roberto Andrés (2016)
This paper seeks to estimate climate risks, threats and vulnerabilities related to flooding produced by the effects of climate change and El Niño Southern Oscilation (ENSO) over the city of Machala and its surroundings. For this purpose, seven meteorological stations trom to Instituto Nacional de Meteorología e Hidrología (INAMHI) that are located around the city, have been studied, two of these stations have daily time series data since more than 30 years. The variables studied correspond to rainfall and maximum and minimum temperatures analyzed with the R-ClimDex program, this data was conjugated with reports of flooding from the Secretaría Nacional de Gestión de Riesgos SNGR (SNGR) and El Niño Index (ONI). The results show that Machala is a city with flooding risk, in which extreme precipitation events are increasing in both intensity and frequency. It´s consistent with the phenomenon of climate change, in addition it was found that flood events are directly related to the occurrence of ENSO. As it relates to the temperature, it was found that the extreme values of minimum temperatures are increasing, more evidence that climate change affects that city plus urban heat pland.